Complex regional telecoupling between people and nature revealed via quantification of trans‐boundary ecosystem service flows. Issue 1 (10th January 2022) - Wang, Yanwen; Hong, Song; Wang, Jinzhu; Lin, Jingyu; Mu, Hang; Wei, Liyuan; Wang, Zhen; Bryan, Brett A.
Abstract: Quantifying and mapping trans‐boundary ecosystem service (ES) flows can help identify dependencies and responsibilities for promoting economic development and environmental sustainability between nations, but few studies have focused on ES flows beyond national boundaries. Our case‐study region—Central Asia—hosts one of the largest dryland areas in the world, and this ecosystem is vulnerable to climate variability and anthropogenic impacts. Understanding ES supply, demand and flows is essential for supporting human wellbeing, livelihoods and economic development. In this study, we mapped the supply, demand and flows of four ES including freshwater provision, food provision, carbon sequestration and cultural (recreation) services between the five Central Asian nations of Kazakhstan, Kyrgyzstan, Uzbekistan, Tajikistan and Turkmenistan for the year 2016. We quantified the spatial patterns in ES supply and demand at local and regional scales, driven by environmental heterogeneity and socio‐economic development, and revealed complex telecoupling of ES flows between nations. Kazakhstan provided the greatest amount of ES to other countries, especially food provision and carbon sequestration, while Uzbekistan was the biggest ES beneficiary, especially from freshwater and food provision services. Our analysis of trans‐boundary ES flows helps to understand the complex telecoupling and rich interdependencies between people and nature between different countries. This information is essential for policy making to balance human and ecological needs, enhance the management of natural capital, and sustain ES provision in our metacoupled world. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.